2008
DOI: 10.1124/dmd.107.020115
|View full text |Cite
|
Sign up to set email alerts
|

The Mibefradil Derivative NNC55-0396, a Specific T-Type Calcium Channel Antagonist, Exhibits Less CYP3A4 Inhibition than Mibefradil

Abstract: ABSTRACT:A novel mibefradil derivative, NNC55-0396, designed to be hydrolysis-resistant, was shown to be a selective than its parent compound, mibefradil, which was withdrawn from the market because of strong inhibition of CYP3A4.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 33 publications
1
20
0
Order By: Relevance
“…In addition, the observed k inact /K i ratio of 2143 ml ⅐ min Ϫ1 ⅐ mol Ϫ1 under the current conditions suggests that CYP3A4 inactivation by mibefradil is approximately 12-fold more potent than reported previously, which places the compound among the most potent P450 inactivators observed to date (Obach et al, 2007). Bui et al (2008) investigated a hydrolysis-resistant analog of mibefradil [(1S,2S)-2-(2-(N-[(3-benzimidazol-2-yl)propyl]-N-methylamino)ethyl)-6-fluoro-1,2,3,4-tetrahydro-1-isopropyl-2-naphthyl cyclopropanecarboxylate dihydrochloride (NNC55-0396)], in which the methoxyacetyl side chain of mibefradil was replaced with a cyclopropylacetyl moiety and observed decreased time-dependent inhibition of CYP3A4. The previous study also demonstrated the inhibitory potential of Ro 40-5966 toward CYP3A4, although not with respect to time-dependent inhibition.…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…In addition, the observed k inact /K i ratio of 2143 ml ⅐ min Ϫ1 ⅐ mol Ϫ1 under the current conditions suggests that CYP3A4 inactivation by mibefradil is approximately 12-fold more potent than reported previously, which places the compound among the most potent P450 inactivators observed to date (Obach et al, 2007). Bui et al (2008) investigated a hydrolysis-resistant analog of mibefradil [(1S,2S)-2-(2-(N-[(3-benzimidazol-2-yl)propyl]-N-methylamino)ethyl)-6-fluoro-1,2,3,4-tetrahydro-1-isopropyl-2-naphthyl cyclopropanecarboxylate dihydrochloride (NNC55-0396)], in which the methoxyacetyl side chain of mibefradil was replaced with a cyclopropylacetyl moiety and observed decreased time-dependent inhibition of CYP3A4. The previous study also demonstrated the inhibitory potential of Ro 40-5966 toward CYP3A4, although not with respect to time-dependent inhibition.…”
Section: Discussionmentioning
confidence: 52%
“…The synthesis of the des-methoxyacetyl metabolite of mibefradil was performed as described previously (Bui et al, 2008;Wu et al, 2008). In brief, 100 mg of mibefradil was dissolved in ethanol-1 N NaOH (50:50) and stirred at room temperature for 4 h. Complete hydrolysis of the ester bond was confirmed by thin-layer chromatography and LC-UV/MS comparison to a mibefradil standard.…”
Section: Introductionmentioning
confidence: 99%
“…With higher concentrations, Ni 2+ and mibefradil wiped out both spiking and burst firings (Figure 4, A and B). We also tested NNC 55-0396, which was reported as a very specific T-channel inhibitor (37)(38)(39). NNC 55-0396 inhibited LVA Ca 2+ currents, turned burst into spiking discharges at low concentration, and wiped out both spiking and burst discharges at high concentration in STN neurons in vitro, all of which were very similar to the effects of Ni 2+ and mibefradil ( Figure 4C).…”
Section: Figurementioning
confidence: 82%
“…3, A and B) suggest that these kinetic schemes will result in log-linear PRA plots. However, there are many examples in the literature of curved PRA plots (He et al, 1998;Voorman et al, 1998;Kanamitsu et al, 2000;Yamano et al, 2001;Heydari et al, 2004;Obach et al, 2007;Bui et al, 2008;Foti et al, 2011). Both quasi-irreversible and partial inactivation kinetics result in concave upward plots (Figs.…”
mentioning
confidence: 99%